A flowsheet-based model approach to reduce water consumption and improve water networks management in the steel sector. Issue 40 (2022) - Zaccara, A.; Petrucciani, A.; Matino, I.; Colla, V.; Ressegotti, D.; Beone, T.; Marchiori, F.; Mosconi, M.; Praolini, F.; Hakala, V.
Abstract: Resource consumption is an important topic for steelmaking industry, which is spending significant efforts to reduce its environmental impact and improve its competitiveness. Water is largely exploited in steelworks for indirect and direct cooling, specific surface treatment, and fumes washing and cooling. It is already reused and recycled after restoring its quality through treatments for temperature and/or pollutant reduction. However, sometimes water networks are not optimized due to outdated water treatments, lack of continuous monitoring, and water network management strategies often based on experience without automation. In recent years, new water treatments, simulation, and optimization tools are becoming available, together with a stronger awareness of the importance of online parameters monitoring. Therefore, improvement of water cleaning, reuse, recycling, and consequent reduction of impact related to water exploitation are potentially achievable. The introduction of innovative treatments must be tested before their implementation in steel plants and the exploration of their behavior in different operating conditions is fundamental. The presented work addresses this topic through the application of several models of operational units, developed in OpenModelica environment and aggregated into a plant simulator. The simulator was used in different case studies related to an Italian plant to assess the impact of new filtering technology for reducing suspended solids on the analyzed water networks and test the effects of different operating configurations on the treatment efficiency. The introduction of new filtration technology leads to environmental and economic advantages due to freshwater intake reduction and water management improvement.